STUDI EKSEGETIS TENTANG KEKUATIRAN MENURUT MATIUS 6:25-34 - Waharman Waharman (Sekolah Tinggi Teologi Arastamar Bengkulu, 2014)
In this article, discuss the words of the Lord Jesus about worries according to Matthew 6: 25-34. The purpose of the Lord Jesus was to advise His disciples so that they would not worry about food, drink and clothing. These words are a motivation for believers in God in matters of food and drink, so that believers are free from all worries and entrust themselves to God in His pets. While still alive in this world, Jesus gave guidelines for living in His care and He also emphasized to His disciples that they first seek the kingdom of God and His truth and all of that will be added to you (Matt. 6:33). Here Jesus does not promise that all believers will become wealthy, but promises the providence of God that meets all the needs of His children, even the glory and riches of heaven. Jesus even used the parable of the birds that were fed by the Father in heaven. If God feeds them, He will also take care of His people. In this article it reminds Christians not only to be concerned about worries, but must surrender fully to God and live in God's care, grateful for God's blessings in an extraordinary way.